Putting African science in the dictionary - Nick Dall (The UNESCO Courier, 2022)
For South African science journalist Sibusiso Biyela, writing about a new dinosaur discovery in his home language Zulu should have been an easy task. But when he sat down to write the piece, as he told the British journal Nature’s podcast, he found that he “didn’t have the words for relatively simple scientific terms like ‘fossil’ or even ’dinosaur’.” Biyela remembers being extremely discouraged.